(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to: Identifying the artificial behavior of kindergarten students. In order to achieve the objectives of the current research, the researcher selected the research community from the students of the Kindergarten Department - College of Basic Education / Al-Mustansiriyah University. The manufactured behavior scale was prepared from (39) items. which consisted of (400) female students from the kindergarten department, and after processing the data statistically, the researcher concluded the following: Kindergarten students are characterized by artificial behavior in a small percentage.